Faerie Winter - Simner, Janni Lee (New York : Random House, 2011)
Unable to get answers from her mother, sixteen-year-old Liza learns from Karin that while her own actions may have doomed the fairy and human worlds, she may be able to save them with more training, if the Faerie Queen can first be stopped.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Fairies -- Fiction; Magic -- Fiction; Mothers and daughters -- Fiction; Coming of age -- Fiction; Fantasy